Improved Systemic Inflammation is Associated with Functional Prognosis in Post-Stroke Patients - Kota Hori; Yoshihiro Yoshimura; Hidetaka Wakabayashi; Fumihiko Nagano; Ayaka Matsumoto; Sayuri Shimazu; Ai Shiraishi; Yoshifumi Kido; Takahiro Bise; Aomi Kuzuhara; Takenori Hamada; Kouki Yoneda; et al. (Annals of Geriatric Medicine and Research)
Background Systemic inflammation is associated with poor functional outcomes. However, the effects of improved inflammation on functional indicators remain unclear. This study aimed to clarify the relationship between improvements in systemic inflammation and activities of daily living in patients after stroke. Methods This retrospective cohort study included patients post stroke with systemic inflammation upon admission. Systemic inflammation was defined as a modified Glasgow Prognostic Score (mGPS) score of 1–2. Improvement in systemic inflammation was defined as a reduction in mGPS score or blood C-reactive protein (CRP) levels during hospitalization. The primary outcomes were the motor items of the Functional Independence Measure (FIM-motor) at discharge. We applied multiple linear regression analysis to examine whether reduced systemic inflammation was associated with outcomes after adjusting for confounding factors. Results Of the 1,490 patients recruited, 158 (median age of 79 years; 88 men) had systemic inflammation on admission and were included in the study. Among these patients, 131 (82.9%) and 147 (93.0%) exhibited reduced mGPS and CRP levels, respectively. The median change in CRP was 2.1 mg/dL (interquartile range, 1.1–3.8). Multivariate analysis revealed that improvements in mGPS (β=0.125, p=0.012) and CRP levels (β=0.108, p=0.108) were independently and positively associated with FIM-motor at discharge. Conclusions Improvement in systemic inflammation was positively associated with functional outcomes in patients post stroke. Early detection and therapeutic intervention for systemic inflammation may further improve outcomes in these patients.